Morbid Mobilities: Смъртоносни мобилности - Hristova, Tsvetelina; Kolev, Anton (Identities: Journal for Politics, Gender and Culture, 2020)
Author(s): Tsvetelina Hristova | Цветелина Христова Title (English): Morbid Mobilities Title (Bulgarian): Смъртоносни мобилности Translated by (English to Bulgarian): Anton Kolev | Антон Колев Journal Reference: Identities: Journal for Politics, Gender and Culture Publisher: Institute of Social Sciences and Humanities - Skopje Page Range: 126-135 Page Count: 10 Citation (English): Tsvetelina Hristova, “Morbid Mobilities,” Identities: Journal for Politics, Gender and Culture, Vol. 17, No. 1 (Summer 2020): 126-135. Citation (Bulgarian): Цветелина Христова, “Смъртоносни мобилности,” превод от английски Антон Колев, Identities: Journal for Politics, Gender and Culture, Vol. 17, No. 1 (Summer 2020): 126-134.